IOT Based Monitoring and Controlling Substation Equipment - Lucky Bharat Pawar; Omkar Vijay Bhoj; Vivek Ravindra Thorat; Pankaj A. Patil (International Journal of Electrical and Communication Engineering Technology, 2025)
The project ”IoT-Based Monitoring and Controlling Substation Equipment” revolves around utilizing the Internet of Things (IoT) technology to make the substation equipment electrical monitoring and control easy. Timely monitoring of these substation equipment is utmost important in ensuring the stable and reliable operation of the power distribution system. This project will design a system whereby sensors collect real-time data on the key parameters such as voltage, current, temperature, humidity, and circuit breaker status of substation equipment. The data is then transmitted wirelessly to a centralized monitoring center through IoT modules, where operators can monitor these parameters. In addition, the system comes with control functionalities that enable the operators to make adjustments in real time from the remote location by either switching the equipment off or on or by changing the operating parameters. This facilitates the remote operation, which will improve the safety at the substation, reduce the inoperable periods, and optimize the schedules for maintenance because actionable information and alerts for preventive maintenance are available. The IoT-based approach gives accuracy about the data, quicker response times, and reduces the level of human intervention that in turn improves the overall efficiency and reliability of the power distribution network. To that extent, this project makes an important leap into the modernization process regarding substation management by using IoT technology.
Keywords: ESP32; IOT; Microcontroller; Oil Level Detection; Web Portal Support